2019
DOI: 10.3390/cells9010059
|View full text |Cite
|
Sign up to set email alerts
|

Polyhexamethylene Guanidine Phosphate Damages Tight Junctions and the F-Actin Architecture by Activating Calpain-1 via the P2RX7/Ca2+ Signaling Pathway

Abstract: Polyhexamethylene guanidine phosphate (PHMG-p), a member of the polymeric guanidine family, has strong antimicrobial activity and may increase the risk of inflammation-associated pulmonary fibrosis. However, the effect of PHMG-p on the barrier function of the bronchial epithelium is unknown. Epithelial barrier functioning is maintained by tight junctions (TJs); damage to these TJs is the major cause of epithelial barrier breakdown during lung inflammation. The present study showed that, in BEAS-2B human bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…S7 online). These data suggest a specific requirement of RIP1 for cell death induced by CDDP, in agreement with the previous reports 25 , 32 , 33 . Moreover, we showed that RIP1 deficiency strongly inhibited CDDP-induced ROS generation irrespective of the presence of EA (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…S7 online). These data suggest a specific requirement of RIP1 for cell death induced by CDDP, in agreement with the previous reports 25 , 32 , 33 . Moreover, we showed that RIP1 deficiency strongly inhibited CDDP-induced ROS generation irrespective of the presence of EA (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have reported that the instillation of PHMG used as a humidifier disinfectant, induces irreversible pulmonary injury and lung fibrosis [ 27 , 44 ]. There were inflammatory macrophage infiltration, bronchiolo-alveolar epithelial hyperplasia and pulmonary fibrosis mainly observed in the terminal bronchioles and alveoli in the lungs of PHMG-loaded mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study found that the PHMG inhalation of mice enhanced macrophage infiltration into the alveolar space, indicating that continuous inflammatory responses by PHMG may contribute to the development of pulmonary fibrosis. Furthermore, PHMG phosphate results in damage of tight junctions and impairment of F-actin architecture integrity in human bronchial epithelial cells [ 44 ]. In the current study, PHMG inhalation stimulated the EMT process and thereby loss of tight junction proteins in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated samples were used as a control group. Sanitizer was diluted with tap water (20 ± 2 • C) to prepare the disinfection Microorganisms 2020, 8,272 3 of 9 solution. The free chlorine concentration was adjusted as desired using a Free Chlorine Test Kit (Lohand, Hangzhou, China).…”
Section: Disinfectionmentioning
confidence: 99%
“…Polyhexamethylene guanidine hydrochloride (PHMG) is a member of the polymeric guanidine family and shows low toxicity. It has broad in vitro bactericidal activity against Gram-positive and Gram-negative bacteria as well as fungi [8]. Its main antibacterial mechanism is collapse of the outer membrane structure, leading to the formation of a pore across the membrane [9,10] and subsequent DNA damage [11].…”
Section: Introductionmentioning
confidence: 99%